Conversion of alkaline characteristics of bauxite residue by mechanical activated pretreatment: Implications for its dealkalization. (1st March 2022) - Wu, Yujun; Jiang, Yifan; Jiang, Jun; Chen, Li; Qin, Xinfeng; William, Hartley; Xue, Shengguo
Abstract: Following the strict environmental policies of various countries, the strong alkalinity of bauxite residue (BR) has become a worldwide problem limiting the sustainable development of the global alumina industry. Continuous conversion of solid-phase alkalinity to free alkali is a major challenge for BR dealkalization to reduce its environmental impact. This work aimed to investigate the effect of mechanical grinding pretreatment on the transformation mechanisms of alkaline solids to free alkali at the BR interface under acids leaching, by monitoring the morphology, phase, and speciation transformations of Al and Si using primarily cross-section scanning electron microscopy−energy dispersive X-ray spectroscopy (SEM-EDS) elemental mapping, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS). The results indicated that particle grinding wrapped some of the alkaline minerals inside the particles to inhibit its release process. The leaching kinetics revealed the order of the buffering effect of minerals against acids leaching is firstly dissolved by minerals containing Na and Ca via the ion-exchange process, followed by Si and Al through the hydrolysis of the desilicated products. The mineral dissemination characteristics and surface compositions further confirmed the undissolved minerals block the interface reaction between embedded alkaline solids and acids to result in the difficult reaction dissolution of alkaline minerals, which is induced by ball milling. This novel approach provides new insight into the efficient dealkalization of BR on a large scale in the industry. Graphical abstract: Image 1 Highlights: Ball milling enhances bauxite residue dealkalization efficiency. Dissemination characteristics of assembly minerals are well revealed. Speciation and conversion of solid alkalinities on residue surfaces are deeply explored. The surface charge behavior of minerals determines the dealkalization process.